(untitled) (World Bulletin of Public Health, 2025)
Endometrial and cervical polyps are common gynecological conditions that frequently affect women and are often associated with hormonal imbalances, inflammatory processes, and mechanical damage. These polyps can arise due to multiple pathological mechanisms, including hormonal dysregulation, chronic inflammation, genetic mutations, and external factors such as medical procedures or infections. Hormonal imbalance, particularly estrogen dominance and progesterone deficiency, plays a key role in the formation of polyps, as it disrupts the normal regeneration of the endometrial lining. Additionally, chronic inflammatory responses contribute to the growth of both endometrial and cervical polyps by increasing cell proliferation and angiogenesis. Genetic factors, including mutations in oncogenes and tumor suppressor genes, can also drive the development of these polyps. The prevention of polyps relies on addressing the underlying risk factors, such as maintaining hormonal balance through diet, exercise, and stress management, preventing chronic infections, and managing metabolic health. Early detection and intervention are crucial for managing polyps and preventing potential complications such as malignancy. This article explores the mechanisms involved in the formation of endometrial and cervical polyps and provides an overview of preventive strategies to mitigate their occurrence